Institutional Pathways to Equity : Addressing Inequality Traps - Bebbington, Anthony J.; Dani, Anis A.; de Haan, Arjan; Walton, Michael (World Bank, Washington, DC, 2012)
Inequalities and development: dysfunctions, traps, and transitions by Anthony J. Bebbington, Anis A. Dani, Arjan de Haan, and Michael Walton. Asset inequality and agricultural growth: how are patterns of asset inequality established and reproduced? By Rachel Sabates. Beneath the categories: power relations and inequalities in Uganda by Joy M. Moncrieffe. Inequalities within India's poorest regions: why do the same institutions work differently in different places? By Arjan de Haan. Indigenous political voice and the struggle for recognition in Ecuador and Bolivia by Jose Antonio Lucero. Cash transfers for older people reduce poverty and inequality by Armando Barrientos. Mineral wealth, conflict, and equitable development by Michael L. Ross. Spain: development, democracy, and equity by Carles Boix.